Complications of Midface Fractures - Lozada, Kirkland; Kadakia, Sameep; Abraham, Manoj T.; Ducic, Yadranko (Facial Plastic Surgery, 2017)
The midface relies on key vertical and horizontal buttresses for proper function and appearance. Trauma to the midface can lead to untoward complications involving critical structures of this area. Many reviews focus on operative management of midface fractures with little focus on complications of the injury and operative repair. We review the current literature on the most common initial and postoperative complications of midface trauma with a specific focus on zygomaticomaxillary complex (ZMC) and Le Fort fracture patterns. A thorough literature review was conducted using PubMed analyzing articles relevant to the subject matter. Various search terms were used to identify articles regarding midface fracture presentation, diagnosis, and management, as well as postoperative complications. Articles were examined by all authors and pertinent information was gleaned for the purpose of generating this review. Disruption of the midfacial buttress system can lead to a significant compromise in form and function. A wide variety of complications are seen in nasal bone fractures, orbital floor fractures, Le Fort, and ZMC fractures. Some fracture patterns can be managed conservatively without operative intervention; however, complications such as loss of facial width/projection, trismus, malocclusion, ocular entrapment, and significant enophthalmos should be managed with open repair. Timing and method of repair depend on patient-specific injury patterns and surgeon preference. Proper management depends on a detailed understanding of the anatomy and pathophysiology of each fracture pattern along with restoration of the patient's premorbid state. Complications of midface fractures result from disruption of the vertical and horizontal buttress support systems. Proper management and repair of midface complications requires a strong understanding of its anatomic basis and pathophysiology. Sequelae from these fractures can be serious and long lasting if not addresses appropriately. Astute diagnosis and timely management can prevent patients from suffering debilitating long-term sequelae.
Keywords: midface fractures; complications; zygomatic complex